Effects of telemonitoring on glycaemic control and healthcare costs in type 2 diabetes: A randomised controlled trial. (October 2018) - Warren, Robin; Carlisle, Karen; Mihala, Gabor; Scuffham, Paul A
Introduction: This study examined the effect of a telehealth intervention on the control of type 2 diabetes and subsequent potential cost-savings to the health system. Methods: This prospective randomised controlled trial randomised adults with type 2 diabetes to the intervention (diabetes program) or control (usual care) arm. Key eligibility criteria included an HbA1c level of at least 58 mmol/mol (7.5%) without severe or unstable comorbidities. All participants continued their usual healthcare, but participants in the intervention arm received additional diabetes care from a diabetes care coordinator via a home monitor that captured clinical measures. Data collected included biomedical, quality of life measures and healthcare (GP, outpatient and inpatient) costs. The primary outcome was HbA1c collected at baseline and 6 months. Analysis was conducted on a complete case intention-to-treat basis. The healthcare system perspective was taken to calculate the incremental cost per percentage-point reduction in HbA1c. Results: Results from 63 participants from each study arm were analysed. HbA1c in the intervention group decreased from a median 68 mmol/mol (8.4%) to 58 mmol/mol (7.5%), and remained unchanged in the control group at median 65 mmol/mol (8.1%) at the 6-month endpoint. The intervention effect on HbA1c change was statistically significant ( p = .004). Total healthcare costs in the intervention group, including the intervention costs, were lower (mean 3781 vs. 4662; p < .001) compared with usual care. Discussion: There was a clinically meaningful and statistically significant benefit from the telehealth intervention at a lower cost; thus, telehealth was cost-saving and produced greater health benefits compared with usual care.